Impact of Risk Production of Laying Hens Livestock in Ringinsari Village, Kandat District, Kediri District - Laily, Dona Wahyuning; Roidah, Ida Syamsu; Rozci, Fatchur; Purnamasari, Ika (Jurnal Ilmu-Ilmu Peternakan, 2023)
Laying hens  farming is one of the livestock industries that has the potential to develop in Indonesia. Raising laying hens, like other agricultural and food businesses, has many potential risks in its operations. The purpose of this research is to identify production risk sources, determine the likelihood of production risk in the aying hen business, and develop a management strategy for each source of risk in the laying hen business. A case study of laying hen breeders in Ringinrejo, Kandat District, Kediri Regency, was used as the research method. This location was chosen with care because it is a viable laying hen production area. Descriptive analysis is used to identify risk sources; z-score analysis is used to determine risk probability; and risk mapping is used for analysis to identify mitigation and prevention strategies. The research results show that the sources of risk found in this study are sources of disease risk and sources of drinking water risk. Production risks of significant value are obtained from disease risk sources, which have a probability value of 83.15% and drinking water has a probability of 13.57%. Alternative strategies, recommended for managing sources of disease risk are prevention strategies including the use of antibiotics and vitamins, as well as mitigation strategies implemented to reduce the occurrence of significant impacts by separating chickens identified as having disease and carrying out treatment. In summary, a prevention strategy is proposed by paying attention to drinking water quality raw materials and making efforts to filter the water to make it sterile.